HOW do we improve the testing of female ballistic body armour? – a comparison of roma plastilina no.1, 10% ballistic gelatine and sebs gel - Malbon, Chris; Knock, Clare; Carr, Debra J. (Springer, 2026)
Body armour designed for use by police officers in England and Wales is currently tested using Roma Plastilina No1 (RP1) as the witness material for the measurement of back face signature (BFS). However, this material has limitations when testing body armour designed for females, as it is not possible to measure the BFS in the breast region due to the way the breast shapes are formed. Therefore, to enable measurement of BFS for females over the breast, an alternative backing material is required to form surrogate breasts and torso which would enable BFS to be measured. A comparison was conducted between RP1, 10% ballistic gelatine and a 30/70% styrene-etylene / butylene-styrene (SEBS) gel, using standardised ballistic test packs and two projectiles: DM11A1B2 9 mm FMJ at velocities 365 ± 10 ms−1; Remington R357M3 0.357” JSP at velocities 390 ± 10 ms−1. The results showed that there was a statistically significant difference identified in measured BFS among the three backing materials with both projectile types. RP1 had the overall smallest variance in measured BFS for both projectile types, however the limitation in being able to mould to create a breast shape is a major limiting factor. With 10% ballistic gelatine, when testing with the 0.357” projectile, a greater variance in measured BFS was shown compared to the other materials. The SEBS gel was consistent for the 0.357” projectile, but with the 9 mm projectile there was greater variance in results. Both 10% ballistic gelatine and SEBS gel would enable a moulded female test form to be created, however SEBS gel has a much longer shelf life and showed resistance to damage, although neither of these materials could be considered as a biofidelic substitute for breast tissue.
Keywords: Legal & Forensic Medicine; 3199 Other biological sciences; 3202 Clinical sciences; 3499 Other chemical sciences; Back face signature (BFS); Behind armour blunt trauma; Breasts; Ballistic gelatine; SEBs